Nilai-Nilai Teologi: Pemberdayaan Jemaat melalui Kerajinan Lidi Kelapa Sawit untuk Meningkatkan Ekonomi di Desa Marbau Selatan Kabupaten Labuhanbatu - Rut Kristina Hutabarat (Jurnal Pengabdian Kepada Masyarakat, 2024)
Economic development can be started by using human resources and natural resources to improve the congregation's economy. The natural resource used is oil palm. Oil palm is a plant that has the benefit of processing its fruit into oil. Apart from the fruit, the stems are also used as particle board. This research aims to find out how empowering congregations through palm oil leaf crafts can improve the economy. The method used in this research is qualitative method . The data collection technique was carried out by means of literature study. From the results of the research that has been carried out, it can be concluded that the presence of natural resources, namely palm oil, can improve the economy through beautiful handicrafts and have community empowerment in them.